Establishment of Reference Center and Policy Advocacy in Department of Medical Services: Suggestions Based on Survey of DMS’s Units - Makarasara, Choosna (Journal of Health Science of Thailand, 2017)
This descriptive study was the third part using results from first two studies on situation analysis as a framework to conduct a survey of institutes under Department of Medical Services (DMS) in order to find out an appropriate approach for DMS to become Reference Center and advocate policy. The study revealed that most of institutes under DMS were aware of the importance of developing the information system but did not have definite target, planning or strategy to become Reference Center and advocate policy. There was no appropriate structure to support and only assigned the tasks to individuals or setting up committee to have the job done. Most of the Individuals assigned for the job, usually temporary employee or government employee working in IT department, did not have appropriate competencies. Information available was usually from within the institute and did not have information at the national level so it did not cover data and information required for becoming Reference Center and advocating policy. The use of data and information mostly was limited to individuals for research work, seldom released to public and lack of extensive integration and analysis of data and information for further use. The major causes of these findings were lack of human resources, budget, appropriate structure and definite information development policy. Suggestions were based on the study on organization development for DMS to become Reference Center and advocate policy. Suggestion included setting up appropriate structure (between Bureau of Strategy. Research and Technology Assessment Institute, ICT Center along with institutes under DMS), setting definite policy and strategy for information development. Arrangement to have definite responsible person and to acquire competence personnel is also crucial.